THE EFFECT OF FINANCIAL LITERACY, EXPERIENCED REGRET AND RISK TOLERANCE INVESTMENT DECISION - Agung Budiyanto; Ratna Purnama Sari (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2023)
This aims of this research is to determine the effect of financial literacy level, experienced regret and risk tolerance on investment decision making. The research used primary data in the form of a questionnaire and distributed to several regions in the Special Region of Yogyakarta Province. The sample was taken by purposive sampling technique with criteria for people who have or are currently investing in real assets or financial assets with 187 respondents as respondents. The data was analyzed using multiple linear analysis. The results of the F test show a number of 36.348 while the t test shows that the financial literacy variable (significance value 0.000) and risk tolerance variable (significance value 0.001) have an effect on investment decision making, while the experienced regret variable (significance value 0.387) has no effect on investment decision making.